Changing lifestyle and demand pattern on pre-prepared food towards Agromas products: Focus in Ipoh, Perak / Akitah Adam - Adam, Akitah (Faculty of Business Management, 2005)
Federal Agricultural Marketing Authority (FAMA) is a marketing agency that was established by government under Ministry of Agricultural on 30 September 1965 and operated under Parliament Act 49,1965 and Parliament Act 141 (amendment) 1974. As a marketing agency, FAMA was built to control, coordinate and improve the marketing activities including agricultural or horticultural such as fruits, vegetables, flowers, beverages, coconuts, fresh water fish, milk, meat and poultry products and others excluding pineapples, rubber, palm oil, and also paddy. FAMA produced their own products, which is known as Agromas brand names. Agromas actually the products manufactured using progressive technology and managed under FAMA's stringent quality control. Our products continually go through quality enhancement in order to meet the requirements of the consumer and market trends. Some of the products are certified by IS09002 hence they maintain exceptional quality and exquisite flavors with the assured advantage of being endorsed halal. For the purpose of this study, the descriptive research will be deployed. Primary data will be obtained from a survey by interviewing using questionnaires to 30 respondents. Most of the secondary data was taken from FAMA annual report, previous research report, related book, magazines and also journal. All the data collected from respondent were transferred onto data sheet by using computer software known as SPSS. Finally, the finding from this study is to conclude whether Agromas products are accepted as pre-prepared food by consumers in Ipoh, Perak. In addition, FAMA should do some improvements in enhancing customer's awareness about their products.